Implementation of Distribution of Cash Social Assistance Funds for Communities Affected by Covid-19 in Subdistricts Lasiana – Kupang City - Eleteria Febiana Hadi; Nikson Tameno; Cicilia A. Tungga (Formosa Journal of Sustainable Research, 2023)
This research was conducted to find out how the distribution of BST funds was implemented for communities affected by Covid-19 in Lasiana Village and also to find out what the driving and inhibiting factors were in distributing this aid. The data used in this research is primary data and also secondary data, which is then analyzed using qualitative descriptive analysis methods. The data collection techniques used in this research used interview, observation and documentation techniques using Edward III's policy implementation theory. The results of this research show that the implementation of BST distribution in Lasiana Subdistrict has not been optimal in accordance with the 4 supporting factors in implementation in accordance with Edward's policy theory which consists of communication which is shown by the existence of an appeal to residents in using aid so that they are wise in using aid but also in conveying related information. The schedule and conditions for distribution of aid have not yet reached all residents who receive aid, then the resources are where human resources in terms of quantity are adequate but in terms of quality are still lacking, the aid has been received by residents and in terms of budget it is sufficient for the needs of residents, then the disposition of the distribution of this aid The implementer's attitude is very good in terms of service and ease in the process of collecting aid, and the bureaucracy of the government concerned is not yet fully on target in distributing this aid because it has not updated the population's social data